Small Regulatory RNA and Legionella pneumophila - Faucher, Sebastien P.; Shuman, Howard A. (Frontiers in Microbiology, 2011)
Legionella pneumophila is a gram-negative bacterial species that is ubiquitous in almost any aqueous environment. It is the agent of Legionnaires’ disease, an acute and often under-reported form of pneumonia. In mammals, L. pneumophila replicates inside macrophages within a modified vacuole. Many protein regulators have been identified that control virulence-related properties, including RpoS, LetA/LetS and PmrA/PmrB. In the past few years, the importance of regulation of virulence factors by small regulatory RNA has been increasingly appreciated. This is also the case in L. pneumophila where three sRNAs (RsmY, RsmZ and 6S RNA) were recently shown to be important determinants of virulence regulation and 79 actively transcribed sRNAs were identified. In this review we describe current knowledge about sRNAs and their regulatory properties and how this relates to the known regulatory systems of L. pneumophila. We also provide a model for sRNA-mediated control of gene expression that serves as a framework for understanding the regulation of virulence-related properties of L. pneumophila.